194 Antecedent Conformity of Diagnostic and Molecular Testing Patterns in Clinical Practice for Newly Diagnosed Acute Myeloid Leukemia With American Society of Hematology and College of American Pathologists Guidelines. (11th January 2018) - George, Tracy; Foucar, Kathryn; Pollyea, Daniel; Erba, Harry; Thompson, Michael; Roboz, Gail; Pagel, John; Cogle, Christopher; Nifenecker, Melissa; Swern, Arlene; Kiselev, Pavel; Sugrue, Mary
Abstract: Background: Newly published guidelines from the American Society of Hematology and College of American Pathologists (ASH/CAP) optimize laboratory testing in patients with newly diagnosed (ND) leukemia. We profiled recent testing patterns in patients with ND acute myeloid leukemia (AML) from academic and community clinical practices to determine antecedent conformity with these guidelines. Methods: Patients with ND AML (n = 259; ≥55 years) were identified from the CONNECT Myelodysplastic Syndrome (MDS)/AML Disease Registry (NCT01688011), a US prospective, observational cohort with ongoing enrollment. Testing patterns up to December 8, 2016, were compared to the ASH/CAP guidelines. Results: Of 27 ASH/CAP guidelines, 18 were relevant to AML and included recommendations on morphologic evaluation, immunophenotyping, karyotyping, and molecular genetic testing. Guideline-recommended morphologic evaluations were performed using bone marrow aspirates in 98.8% of patients and reported for cellularity (92% of patients); fibrosis (44%); ring sideroblasts (51%); Auer rods (39%); and granulocytic (27%), megakaryocytic (36%), and erythroid dysplasia (40%). Recommended cytogenetic, molecular, and fluorescence in situ hybridization (FISH) analyses were reported in 92.7%, 66.8%, and 79.5% of patients, respectively. Molecular or FISH testing, without karyotyping, occurred in only 5.4% of patients. When molecular analyses were performed (n = 173), guideline conformance varied with only 75.7% of patients tested for FLT3-ITD, 21.4% for IDH1, 20.2% for IDH2, and 12.7% for TP53. Only 8.7% of patients were tested for all recommended mutations. Molecular analyses performed in seven of 11 (63.3%) patients with core-binding factor (CBF) AML included KIT testing in four of seven (57.1%) patients. When AML was not associated with CBF or myelodysplasia-related changes (124/259 [47.9%]), recommended tests for NPM1, CEBPA, and RUNX1 were performed in 75.8%, 50.8%, and 15.3% of patients, respectively. Conclusions: Current laboratory testing for ND AML do not conform to the new ASH/CAP guidelines. The CONNECT, MDS/AML registry is uniquely positioned to document evolving conformity after guideline publication.